The extinction of 'intra-group' debt : a case study analysis of the interaction between sections 8(4)(m) and 20(1)(a)(ii) and the applicability of the eighth schedule to the Income Tax Act 58 of 1962 - Huisamer, Dirk Esau (Department of Commercial Law, 2015)
Includes bibliographical references.